(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
Ecology is an independent science that belongs to the category of Biological Sciences.The living conditions of utiric organisms and the living conditions of these organisms themselves are inhabited byhit, which studies the complex relationships between them and the laws that are born on this basis